(untitled) (Research, Society and Development, 2021)
The Bertioga Canal is bounded by the continent and the island of Santo Amaro, constituting the natural unit that connects the municipalities of Santos, Guarujá and Bertioga with the ocean. It is considered as one of the most visited regions by recreational fishermen in the state of São Paulo. The present research analyzed changes in the practice of recreational fishing for snooks, in the Bertioga channel, resulting from the impacts of the pandemic of COVID-19. Between February and April 2021, a boarding point located in the southern section of this channel was visited, to inventory the conditions and services offered to recreational fishermen in the region, during the period of restriction caused by the pandemic of COVID-19. In this location, the main services are boat rentals and outboard engines, in addition to selling shrimp as live bait. In the period of the closing of the retail trade, boats were rented more frequently to recreational fishermen, on days that, frequently, there was not great exercise of this activity, as on weekdays of the week. Reports of the intense movement of boats, which travel above the permitted speed (5 knots) destabilizing the margins and vegetation of the mangrove were pointed out as an impact of the restriction period. Irregular fishing, using “malhão” nets, has also caused environmental damage, with the reduction of the aquatic biodiversity in the channel. We emphasize the performance of public policies in the sector, guaranteeing health, food security and income generation, mitigating the crisis and recovering local economies.